1979
DOI: 10.1152/ajprenal.1979.237.6.f433
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin-induced renal hemodynamic alterations: renin and prostaglandin relationships

Abstract: The present studies examined the role of the renin-angiotensin system as a modifier of the renal vasomotor response to bradykinin. Renal arterial bradykinin infusion (80 ng.kg-1.min-1) initially resulted in increased renal blood flow (RBF). The secretory rates of renin and prostaglandins increased after 60 min. With continued bradykinin administration (120 min) RBF and prostaglandin secretory rates returned toward control values, although renin secretory rate remained elevated (P less than 0.02). After prostag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

1980
1980
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 0 publications
0
13
1
Order By: Relevance
“…Previous studies examining the renal hemodynamic and excretory effects of exogenous bradykinin were performed by renal arterial infusion. 8 " 10 This route of infusion may not mimic a physiological route of kinin delivery, because intrarenally formed kinins must reach the vasculature via the interstitium. To address this problem, we have recently developed an infusion technique in our From laboratory by which compounds can be infused and localized in the renal medullary interstitium.…”
Section: Orphological and Functional Data Indicate Thatmentioning
confidence: 99%
“…Previous studies examining the renal hemodynamic and excretory effects of exogenous bradykinin were performed by renal arterial infusion. 8 " 10 This route of infusion may not mimic a physiological route of kinin delivery, because intrarenally formed kinins must reach the vasculature via the interstitium. To address this problem, we have recently developed an infusion technique in our From laboratory by which compounds can be infused and localized in the renal medullary interstitium.…”
Section: Orphological and Functional Data Indicate Thatmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Previous studies have shown that kallikrein from the connecting tubule enters the vascular space 9 -11 as well as the interstitium, 8 where it produces bradykinin. Thus, both plasma bradykinin and interstitial bradykinin may be significant regulators of afferent arteriole resistance.…”
mentioning
confidence: 99%
“…Key Words • bradykinin • kallikrein • angiotensins • blood pressure • mineralocorticoids lease, 13 whereas an opposite effect reportedly occurs after administration of aprotinin, a nonspecific inhibitor of renal kallikrein. 14 In the vasculature, the intrinsic kallikrein-kinin system 8 19 Although these data need to be confirmed, it is tempting to speculate that in vivo stimulation of kinin generation by Ang II could restore the balance between these functionally opposite hormones.…”
mentioning
confidence: 99%